Smoking Behavior among Undergraduate Female Students in Universitas Padjadjaran Bandung - Rafsae Iqbal Akbar; Arifah Nur Istiqomah; Irvan Afriandi (Faculty of Medicine Universitas Padjadjaran, 2019)
Background: Smoking is an addictive habit of affecting human behavior. Global data has shown that 47.5% of men and 10.3% of women are active smokers. Based on Survei Sosial Ekonomi Nasional in 2007, the prevalence of women smokers in Indonesia is increased from 1.3% to 5.2%. This study was conducted to describe the smoking behavior among undergraduate female students in Universitas Padjadjaran, Bandung.Methods: This was a descriptive cross-sectional study, including female students from 9 faculties in Universitas Padjadjaran, using a snowball sampling technique. A self-administered questionnaire was distributed, consisting of questions about when students smoked for the first time, level of addiction, smoking intensity, smoking location, and the affecting mood.Result: Of 99 female students, 40.40% have started smoking in high school, 31.32% in the university, and 25.25% in junior high school. The smoking intensity was moderate (45.45%), but some were high (29.30%). The location preference for smoking was both in private and public places (88.89%), driven by both positive and negative moods (88.89%). Interestingly, the most addiction level was situational (34.34%) or intensive (34.34%).Conclusions: Since most of the female students have started smoking before enrolling in the university, smoking education and cessation in junior high school need to be strengthened.